2016
DOI: 10.1038/emi.2016.82
|View full text |Cite
|
Sign up to set email alerts
|

flrA,flrBandflrCregulate adhesion by controlling the expression of critical virulence genes inVibrio alginolyticus

Abstract: Adhesion is an important virulence trait of Vibrio alginolyticus. Bacterial adhesion is influenced by environmental conditions; however, the molecular mechanism underlying this effect remains unknown. The expression levels of flrA, flrB and flrC were significantly downregulated in adhesion-deficient V. alginolyticus strains cultured under Cu2+, Pb2+, Hg2+ and low-pH stresses. Silencing these genes led to deficiencies in adhesion, motility, flagellar assembly, biofilm formation and exopolysaccharide (EPS) produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
62
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 51 publications
1
62
0
1
Order By: Relevance
“…In V. cholerae, the FlrA regulon has been limited in flagellum-coding genes to date, and the FlrA regulation of flagellum synthesis seems unaffected by FlhG (26). The deficiency of FlrA in Vibrio results in the altered expression of some virulence genes and binding to epithelial cells, while it is still unclear whether FlrA directly regulates the transcription of these genes (35,36). In contrast, FleQ in P. aeruginosa regulates many biofilm-related genes, such as pel and psl for exopolysaccharide synthesis and cdrAB, coding for an adhesin.…”
Section: Discussionmentioning
confidence: 99%
“…In V. cholerae, the FlrA regulon has been limited in flagellum-coding genes to date, and the FlrA regulation of flagellum synthesis seems unaffected by FlhG (26). The deficiency of FlrA in Vibrio results in the altered expression of some virulence genes and binding to epithelial cells, while it is still unclear whether FlrA directly regulates the transcription of these genes (35,36). In contrast, FleQ in P. aeruginosa regulates many biofilm-related genes, such as pel and psl for exopolysaccharide synthesis and cdrAB, coding for an adhesin.…”
Section: Discussionmentioning
confidence: 99%
“…It is an opportunistic pathogen and a major cause of vibriosis in aquatic animals, resulting in severe economic losses worldwide (6,7). Recent studies suggested that V. alginolyticus is also a potential human pathogen (8).…”
mentioning
confidence: 99%
“…clpC is thought to serve as a molecular chaperone with a significant role in Bacillus subtilis sporulation (Nanamiya et al., ). As bacterial adhesion to the host surface is critical for pathogen invasion (Chen et al., ; Luo et al., ), it is important that probiotics compete with pathogens for adhesion sites. Flagella are reported to be important for bacterial adhesion (Qin et al., ; Wang et al., ).…”
Section: Discussionmentioning
confidence: 99%